Case Report: Primary Bilateral Minimally Invasive Adenocarcinoma of the Lungs in an 11-Year-Old Child: A Rare Case - Lei, Xing; Zheng, Yongfei; Zhang, Guohua; Zheng, Hailan (Frontiers in Surgery, 2021)
There are many types of benign and malignant tissue, but primary lung tumor is very rare in children [1] and often remains undiagnosed until after distant metastasis has occurred [2, 3]. Few cases of early lung adenocarcinoma in children have been reported. However, this case concerns an 11-year-old child with primary bilateral minimally invasive adenocarcinoma. As far as we know, this is the youngest reported case of its type.